The Effect of Soil Tillage, Intermittent Irrigation, and Fertilization on Productivity of Newly Open Rice Fields on Inceptisols and Ultisols from Muarabeliti and Tatakarya - DEDI NURSYAMSI; L.R WIDYOWATI; DIAH SETYORINI; J. SRI ADININGSIH (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2000)
Field experiment was conducted to study the effects of soil tillage, intermittent drainage, and fertilization on productivity of newly open rice fields of Inceptisols in Muarabeliti, South Sumatra and Ultisols in Tatakarya, Lampung. The experiment was carried out using split plot design with 3 replications. Two varieties of rice IR-42 and Ciliwung were used as plant indicators in Muarabeliti and Tatakarya, respectively. The main plots consist of combination of soil tillage and irrigation treatments: (1) no soil tillage/flooded continuously, (2) soil tillage/flooded continuously, (3) no soil tillage/intermittent drainage, and (4) soil tillage/intermittent drainage. The treatments on sub plot were : (1) no fertilization, (2) application of organic matter (rice straw) of 5,000 kg/ha, (3) application of K fertilizer (KCI) of 150 kg/ha, and (4) application of K fertilizer (KCI) of 150 kg/ha and dolomite of 50 kg/ha. The results showed that there were no significant effets of soil tillage treatment on soil chemical characteristics, nutrients uptake, plant growth, and dry straw and grain yield. However, in Ultisols of Tatakarya, dry straw and grain yields were better with soil tillage than no soil tillage treatment. Intermittent drainage treatment decreased soil exchangeable Ca and K in Inceptisols of Muarabeliti under soil tillage condition. While in Ultisols of Tatakarya, the treatment decreased soils exchangeable Ca, K and also Mg and base saturation under with and without no soil tillage treatments. The use of 5,000 kg/ha rice straw increased soil organic-C, exchangeable K, K-HCI, and cation exchange capacity; plant K uptake; and dry straw and grain yield in both soils. Application of K fertilizer of 150 kg/ha and its combination with dolomite of 50 kg/ha, each increased soil K-HCI, exchangeable K, and dry grain yield in Inceptisols of Muarabeliti. While in Ultisols of Tatakarya each treatment increased the above parameters and dry straw yield .